Intra‐pulmonary arteriovenous anastomoses and pulmonary gas exchange: evaluation by microspheres, contrast echocardiography and inert gas elimination. (26th September 2019) - Stickland, Michael K.; Tedjasaputra, Vincent; Seaman, Cameron; Fuhr, Desi P.; Collins, Sophie É.; Wagner, Harrieth; van Diepen, Sean; Byers, Bradley W.; Wagner, Peter D.; Hopkins, Susan R.
Abstract : Key points: Imaging techniques such as contrast echocardiography suggest that anatomical intra‐pulmonary arteriovenous anastomoses (IPAVAs) are present at rest and are recruited to a greater extent in conditions such as exercise. IPAVAs have the potential to act as a shunt, although gas exchange methods have not demonstrated significant shunt in the normal lung. To evaluate this discrepancy, we compared anatomical shunt with 25‐µm microspheres to contrast echocardiography, and gas exchange shunt measured by the multiple inert gas elimination technique (MIGET). Intra‐pulmonary shunt measured by 25‐µm microspheres was not significantly different from gas exchange shunt determined by MIGET, suggesting that MIGET does not underestimate the gas exchange consequences of anatomical shunt. A positive agitated saline contrast echocardiography score was associated with anatomical shunt measured by microspheres. Agitated saline contrast echocardiography had high sensitivity but low specificity to detect a ≥1% anatomical shunt, frequently detecting small shunts inconsequential for gas exchange. Abstract: The echocardiographic visualization of transpulmonary agitated saline microbubbles suggests that anatomical intra‐pulmonary arteriovenous anastomoses are recruited during exercise, in hypoxia, and when cardiac output is increased pharmacologically. However, the multiple inert gas elimination technique (MIGET) shows insignificant right‐to‐left gas exchange shunt in normal humans and canines. To evaluate this discrepancy, we measured anatomical shunt with 25‐µm microspheres and compared the results to contrast echocardiography and MIGET‐determined gas exchange shunt in nine anaesthetized, ventilated canines. Data were acquired under the following conditions: (1) at baseline, (2) 2 µg kg −1 min −1 i.v. dopamine, (3) 10 µg kg −1 min −1 i.v. dobutamine, and (4) following creation of an intra‐atrial shunt (in four animals). Right to left anatomical shunt was quantified by the number of 25‐µm microspheres recovered in systemic arterial blood. Ventilation–perfusion mismatch and gas exchange shunt were quantified by MIGET and cardiac output by direct Fick. Left ventricular contrast scores were assessed by agitated saline bubble counts, and separately by appearance of 25‐µm microspheres. Across all conditions, anatomical shunt measured by 25‐µm microspheres was not different from gas exchange shunt measured by MIGET (microspheres: 2.3 ± 7.4%; MIGET: 2.6 ± 6.1%, P = 0.64). Saline contrast bubble score was associated with microsphere shunt (ρ = 0.60, P < 0.001). Agitated saline contrast score had high sensitivity (100%) to detect a ≥1% shunt, but low specificity (22–48%). Gas exchange shunt by MIGET does not underestimate anatomical shunt measured using 25‐µm microspheres. Contrast echocardiography is extremely sensitive, but not specific, often detecting small anatomical shunts which are inconsequential for gas exchange. Key points: Imaging techniques such as contrast echocardiography suggest that anatomical intra‐pulmonary arteriovenous anastomoses (IPAVAs) are present at rest and are recruited to a greater extent in conditions such as exercise. IPAVAs have the potential to act as a shunt, although gas exchange methods have not demonstrated significant shunt in the normal lung. To evaluate this discrepancy, we compared anatomical shunt with 25‐µm microspheres to contrast echocardiography, and gas exchange shunt measured by the multiple inert gas elimination technique (MIGET). Intra‐pulmonary shunt measured by 25‐µm microspheres was not significantly different from gas exchange shunt determined by MIGET, suggesting that MIGET does not underestimate the gas exchange consequences of anatomical shunt. A positive agitated saline contrast echocardiography score was associated with anatomical shunt measured by microspheres. Agitated saline contrast echocardiography had high sensitivity but low specificity to detect a ≥1% anatomical shunt, frequently detecting small shunts inconsequential for gas exchange.